Genetic and Phenotypic Characteristics of Congenital Hypothyroidism in a Chinese Cohort - Long, Wei; Guo, Fang; Yao, Ruen; Wang, Ying; Wang, Huaiyan; Yu, Bin; Xue, Peng (Frontiers in Endocrinology, 2021)
Background The molecular etiology and the genotype–phenotype correlation of congenital hypothyroidism (CH) remain unclear. Methods We performed genetic analysis in 42 newborns with CH using whole-exome sequencing. Patients were divided into a single-gene group and a multi-gene group according to the number of affected genes, or divided into a monoallelic group, a biallelic group, and an oligogenic group according to the pattern of the detected variants. The clinical characteristics were compared between groups. Results Thyroid dysgenesis (TD) was observed in 10 patients and goiter in 5 patients, whereas 27 patients had normal-sized gland-in-situ (GIS). We identified 58 variants in five genes in 29 patients. The genes with the most frequent variants were DUOX2 (70.7%), followed by TSHR (12.1%), DUOXA2 (10.3%), and TPO (5.2%). Variants in the genes causing dyshormonogenesis (DH) were more common than those in the genes causing TD (87.9% versus 12.1%). Among the patients with detected variants, 26 (89.7%) were harboring a single gene variant (single-gene group), which include 22 patients harboring biallelic variants (biallelic group) and four patients harboring monoallelic variants (monoallelic group). Three (10.3%) patients harbored variants in two or three genes (multi-gene group or oligogenic group). Compared with the single-gene group, the levothyroxine (L-T4) dose at 1 year of age was higher in the multi-gene group (p = 0.018). A controllable reduction in the L-T4 dose was observed in 25% of patients in the monoallelic group and 59.1% of patients in the biallelic group; however, no patients with such reduction in the L-T4 dose were observed in the oligogenic group. Conclusions Patients with normal-sized GIS accounted for the majority of our cohort. Genetic defects in the genes causing DH were more common than those in the genes causing TD, with biallelic variants in DUOX2 being dominant. DH might be the leading pathophysiology of CH in Chinese individuals.